CLINICAL THERAPEUTIC STUDY AND TREATMENT OF ORAL MUCOSA AFTER CHEMOTHERAPY (International Conference on Medical Science, Medicine and Public Health, 2025)
Oral mucositis continues to be one of the most severe and frequently reported complications of anti-cancer treatment, significantly reducing the quality of life of cancer patients. The development of mucositis leads to the interruption of anti-cancer treatment courses, thereby reducing their effectiveness, which has a negative impact on the prognosis of the disease. In addition, mucositis significantly increases the costs of treating cancer patients and prolongs the duration of hospitalization.In this regard, there is a need to search for and develop highly effective means of prevention and treatment of various forms of oral mucositis in order to increase the effectiveness of antitumor treatment of cancer.Today, the existing methods of prevention and treatment of oral mucositis are not effective. The methods described in the literature are often complex, multi-component, and require the use of expensive oral